Determinants of assault-related violence in the community: potential for public health interventions in hospitals. Issue 12 (16th August 2013) - Ramsay, S E; Bartley, A; Rodger, A J
Abstract : Background: Data from emergency departments (EDs) in England describe the epidemiology of violent assaults. However, the potential of such data to inform hospital-based public health interventions remains unknown. Objective: To identify determinants of assaults using ED data to inform development of programmes delivered in acute Trusts for reducing assault-related injuries in the community. Methods: Data were collected from a large North London acute Trust on assault-related injuries reporting to A&E over 18 months (July 2010–February 2012). Information was recorded on patient demographics and assaults (place of assault, type of assault, relation to assailant) through questionnaires administered by ED reception staff. Results: 1210 assaults were recorded between July 2010 and February 2012. 18% of assaults were severe (strangling, stabbings, sexual assaults). 75% of assault victims were men, 37% were young adults (20–30 years) and 15% were teenagers. A higher proportion of victims lived in more deprived areas. Apart from public streets (48%), the main location of assaults was at home (20%). Female compared with male victims were significantly more likely to be both assaulted at home (OR 6.13; 95% CI 4.41 to 8.54) and to be assaulted by a known assailant (family member, friend, partner/ex-partner; OR 8.20, 95% CI 5.85 to 11.48). Conclusions: The results highlight the notable contribution of domestic violence to assaults presenting to hospital ED. Such findings can be used to plan interventions such as screening hospital patients for domestic violence. ED data have the potential to inform hospital-based initiatives to address issues such as assaults in the local population.